The role of counseling for non-traditional students in formal higher education: a scoping review - Stamou, Panagiota; Tsoli, Konstantina; Babalis, Thomas (Frontiers in Education, 2024)
Introduction Since the mid-20th century, the number of adult students enrolled in formal higher education (HE) programs has significantly increased. The profile of non-traditional students differs significantly from that of traditional students in terms of their characteristics, learning methods, obstacles and challenges, motivations for learning, and conditions for effective learning. Unlike traditional students, adult students often balance family, work, and educational responsibilities, necessitating a more nuanced approach to support and guidance. However, most HE institutions primarily serve the needs of traditional student populations, which results in limited support available to adult students. This scoping review aimed to explore and map the existing literature on the role of adult (or non-traditional) students counseling in the context of formal HE. Methods We focused on literature related to academic advising for non-traditional students in formal HE, restricting our search to both empirical and non-empirical articles published in peer-reviewed journals between 2010 and 2022. Employing Arksey and O’Malley’s scoping review method and the PRISMA-ScR Checklist, we searched four databases (EBSCOhost, Crossref, Semantic Scholar, and ERIC), supplemented by a manual search. Results Of the 1,330 articles identified and screened, 25 studies met the eligibility criteria. Our review included 17 empirical and eight non-empirical studies, with the majority conducted in the USA (21 of 25). Thematic analysis revealed five key research areas (or themes): academic advising practices, perceptions of advising, technology, and advising, advising models, and academic success. The most common research theme, advising practices for adult (undergraduate and doctoral) students, constituted 52% of the studies (n = 13). Discussion Drawing from our analysis, we discuss current trends and future development in advising non-traditional students within formal HE settings. The added value of academic advising for adult students is explored, and any potential gaps in research literature knowledge are identified.